Subacute NO generation induced by Alzheimer's beta-amyloid in the living brain: reversal by inhibition of the inducible NO synthase - Ishii, Kenji; Muelhauser, F.; Liebl, Ulrike; Picard, Martin; Kühl, Sandra; Penke, B.; Bayer, T.; Wießler, Manfred; Hennerici, Michael G.; Beyreuther, Konrad; Hartmann, Tobias; Faßbender, Klaus (The FASEB journal, 2000)
Glial activation contiguous to deposits of amyloid peptide (Abeta) is a characteristic feature in Alzheimer's disease. We performed complementary in vitro and in vivo experiments to study the extent, kinetics, and mechanisms of microglial generation of nitric oxide (NO) induced by challenge with Abeta. We showed that Abeta fibrils dose-dependently induced a marked release of stable metabolites of NO in vivo that was strikingly similar regarding extent and temporal profile to the one in the parallel designed microglial cell culture experiments. However, costimulation with interferon gamma, which was a prerequisite for Abeta-induced NO generation in vitro, was not required in vivo, demonstrating that factors are present in the living brain that activate glial cells synergistically with Abeta. Therefore, in Alzheimer's disease, deposits of Abeta fibrils alone may be sufficient to induce a chronic release of neurotoxic microglial products, explaining the progressive neurodegeneration associated with this disease. Our observation that systemic administration of selective iNOS inhibitors abolishes Abeta-induced NO generation in vivo may have implications for therapy of Alzheimer's disease.